The predictive value of prognostic nutritional index on early complications after robot-assisted radical cystectomy - Wang, Yiduo; Lu, Xun; Gao, Yue; Liu, Ning; Jiang, Hua; Chen, Shuqiu; Chen, Ming (Frontiers in Surgery, 2022)
Objective: The purpose of the study was to evaluate the predictive value of prognostic nutritional index (PNI) on early complications (within 30-day) after robot-assisted radical cystectomy (RARC) and urinary diversion. Patients and methods: Patients underwent RARC and urinary diversion between November 2018 and December 2021 in our centre were screened in this retrospective study. Baseline characteristics and perioperative data were recorded. Early complications after surgery were classified according to Clavien-Dindo system. Univariate and multivariate logistic analysis were performed to decide the potential factors associated with post-RARC complications. The receiver operating characteristic (ROC) curve was conducted to determine the predictive value of PNI on early overall and major complications after RARC. Results: Overall 139 men and 13 women with a median age of 69 years and mean BMI of 24.4 kg/m2 were included in this study. As for urinary diversion, most patients (n=111, 73%) received cutaneous ureterostomy, 36 patients (23.7%) underwent orthotopic neobladder and 5 patients (3.3%) received ileal conduit. The incidence of postoperative complication rate was 44.7%, which included 82.2% minor complications and 17.8% major complications. Further univariate and multivariate logistic analysis demonstrated that hypertension (OR=2.96, 95%CI:1.24-7.07, P=0.015), PNI (OR=0.73, 95%CI: 0.62-0.86, P < 0.001), and CCI (OR=1.44, 95%CI: 1.01-2.06, P=0.047) were independent risk factors of early complications after RARC. Moreover, PNI (OR=0.72, 95%CI: 0.60-0.86, P < 0.001) was also the predictor of major complications after RARC. The ROC curve demonstrated that PNI (AUC = 0.829; AUC = 0.840) has a great predictive value in early overall and major complications after RARC. Conclusion: PNI can be an early alert for RARC patients thus aiding in closer monitoring and postoperative management.